Estimation of total carbon stock of Kakinada mangrove using normalized difference vegetation index, East Godavari, Andhra Pradesh - Katiyar, M.; Yadav, V.; Selvi, VA (Indian Forester, 2020)
Mangroves hold a significant amount of carbon and play a critical role in the earth's climate system. To this date, carbon stock had never been estimated for Kakinada mangroves with NDVI especially in Coringa which has been affected by disturbances (e.g.: Gathering Fuelwood, Fish Farming, and Prawn Farming). Understanding the multi-temporal dynamics of carbon stocks over Kakinada forests is very crucial because previous land use land cover change activities have modified the land for unsustainable aquaculture. During the study, we described arobust approach to estimate the carbon content of mangroves by using Normalized Difference Vegetation Index features. Normalized Difference Vegetation Index has features based on nearinfrared spectrum absorption for the different vegetation classes. Further sliced Normalized Difference Vegetation Index values from 0.15 to 0.64 have been used to calculate the aboveground biomass stock and belowground biomass stock which was afterward concluded as total carbon stock. Normalized Difference Vegetation Index based estimation of aboveground carbon stock results as 41.311 ±13 Mg ha-1, whereas belowground carbon estimated as 71.382 ± 20 Mg ha-1. Final results for Total carbon calculated by AGC and BGC is 112.694 ± 26 Mg ha-1. Additionally, linear regression analysis shows positive Skewness between the NDVI and the carbon stock. The Pearson correlation was calculated based on the independent (Carbon values) and dependent variable (NDVI) results in a value of 0.95.